PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 036 SINTONG KECAMATAN TANAH PUTIH - Yuslita Yuslita; Zulkifli Zulkifli; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is IPA student learning outcomes is still considered low because students are still difficulties in accepting the lessons, students are less active in participating in the lesson, the teacher is less engaging students in learning. This research aims to improve learning outcomes IPA third grade students SD Negeri 036 Sintong which number of students is 18 students. This research was conducted by II cycles, each cycle consisting of two meetings with one daily tests. Results of the data analysis activities of teachers in the first meeting cycle I is 45.83% and the second meeting increased to 54.16%. In the first meeting cycle II is 70.83% and increase to 87.5% at the second meeting of cycle II. From the results of this study showed student activities data at the first meeting of the first cycle was 45.83% and in the second meeting increased to 58.33%. At the first meeting of the second cycle was 75% and at the second meeting of the second cycle increased to 83.33%. From the results of this study showed that student learning has increased the average student learning outcomes in basic score is 56.88 increase in cycle I to 70.65 and increased again in Cycle II to 76.39. For mastery learning on the base score is 44.44% increase in cycle I to 66.67% and increased again in Cycle II become 88.89%. Thus we can conclude that if implemented cooperative learning model type Student Teams Achievement Divisions (STAD) can improve IPA learning outcomes third grade students SD Negeri 036 Sintong Kecamatan Tanah Putih.Keywords: Cooperative Learning Type Student Teams Achievement Divisions (STAD), IPA Learning Outcomes